Film Festival/Film History: The Impact of Film Festivals on Cinema Historiography. Il cinema ritrovato and beyond - Di Chiara, Francesco; Re, Valentina (Cinémas)

(untitled) (Cinémas, 2011)
The aim of this essay is to offer some coordinates for the analysis of the impact of film festivals on cinema historiography. Although film festivals have had a pivotal role in film studies since the 1940s in determining various aspects of research interests, both on a critical and theoretical level, it is only in recent years that they have gathered academic attention as an autonomous research field. Moreover, even among most studies of film festivals, the relationship between film festivals and cinematic historiography seems to have been overlooked. This essay is conceived, therefore, as a provisional contribution, attempting to delineate the scope of the topic and set some parameters for further research. After defining what we mean by the impact of film festivals on cinema historiography, we try to construct a conceptual framework, capable of examining how the strategies deployed by film festivals—such as their structure, schedules, published materials and round tables, as well as their identification of a target audience—implicitly highlight the potential impact of film festivals on cinema historiography. To exemplify our theoretical statements, we refer to different kinds of film festivals and, more particularly, make a few remarks about a very particular case, Il cinema ritrovato in Bologna.